Statistical abstract - Uganda Bureau of Statistics (Entebbe, Uganda : Uganda Bureau of Statistics, 2005)
Abstract is Uganda's most popular single source of Statistics on the Social, Financial and Economic issues.
Latest issue consulted: 2005
Keywords: Uganda -- Statistics -- Periodicals